Pengaruh Perputaran Kas Terhadap Profitabilitas Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2015-2020 - Oktaviana Santuri; Arlis Dewi Kuraesin (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
The purpose of this study was to determine how the effect of cash turnover and on profitability, either partially on Manufacturing companies listed on the Indonesia Stick Exchange in 2015-2020. The data used in this study used secondary data. The sample of this study was determined by purposive sampling, so that 42 samples of companies were obtained for 6 years of observation (2015-2020) with 252 observations. The data analysis technique used is data analysis. The first is descriptive statistics, classical assumption test, multiple regression analysis and Hypothesis testing. The results of the study partially show that cash turnover has a positive and significance value of 0,043 which is smaller than α = 0,05.